Research Trends into Support for Families Coping with Dementia in Japan (International Journal of Studies in Nursing, 2017)
In Japan, there is a growing need for family support of elderly patients with dementia because the number of sufferers is expected to increase over coming years. We conducted a review of 92 studies into the support provided to the families of patients with dementia in Japan. They were reviewed by care setting, study focus, and study design. Most studies were in home settings, followed by hospital settings, with the fewest in long-term care facilities. A wide range and quality of studies were performed in home settings, including quantitative descriptive and interventional studies; however, qualitative descriptive studies and case studies predominated. We identified a need to perform additional studies to verify support programs at home. Concerning family support in hospitals, studies were mainly performed in relation to early diagnosis of dementia and early discharge from hospital, and we observed a clear need to investigate the development of new support programs. Finally, although the need for family support is estimated to be high in long-term care facilities, we found only a few studies investigating this issue. In particular, more studies are needed on the topic of end-of-life care. To offer support that meets the needs of families in various care settings, there is an urgent need to accumulate evidence about patients and their families in each setting.